Culture-based studies’ topography in the modern French social science - B. E. Nosenok, (Ukrainian Cultural Studies, 2019)
Cultural studies as a humanities researcher takes the place of an expert. The relevance of this topic is due to the lack of development of the issues of “culture-based studies” in Ukrainian culturology. There is a lack of translated into French or Ukrainian languages of French sources published since 1975. French culturological science, which developed after 1975, is almost not represented in Ukrainian culturology. The present stage of the development of French historiography, which lies at the heart of cultural history, and cultural studies, is associated with increased attention to social knowledge. This stage is characterized by the deployment of a “critical turn”, which proceeds from the following principles: the interdisciplinary approach, the significance of cultural expertise, the severity of publications and the multiplicity of their forms, multidisciplinarity. The “critical turn” affects the following spheres of knowledge: la Culturologie, les Études culturelles, les Sciences de la Culture. The article substantiates the relevance of the use of the concept of “culture-based studies” to the definition of processes that are unfolding within the framework of French humanities and are associated exclusively with the theoretical formations in the context of the social sciences. The purpose of the article is to outline a map of culture-based studies in the field of French humanitaristics. The methodology of the article is based on the application of interdisciplinary and multidisciplinary approaches to research in the field of culturology. Also, methodological developments in the field of “critical turn” and the achievements of the sociological circle and the interdisciplinary discussion club “Eranos” were applied. The scientific novelty of the article is to substantiate the appropriateness of the use of the concept of “culture-based studies” on the definition of processes that are unfolding within the framework of French humanitaristics and relate exclusively to theoretical formations in the context of social sciences. This concept to the field of Ukrainian culturology is introduced for the first time. Also, for the first time, the place and forms of culturology in French humanities were clarified. Conclusions. Working with a source base and methodology is one of the points that are compulsory on the way to the solution of the tasks, the main of which is the formation of the body of fundamental works for French history (including the history of culture) and historiography of the period since 1975 year to the present day. On the basis of this building, there is the prospect of building an alternative national cultural history project addressed to the vector of the French historiographical, historical-anthropological and cultural-related issues in the field of social knowledge. The article presents the arguments why it is appropriate to use the concept of “culture-based studies” in the context of conducting research in relation to French humanitaristics, in particular, the modern period of its development.
Keywords: “culture-based studies”, history of culture, “critical turn”, “new history”, interdisciplinarity, social knowledge, “cultural history”